Ativação de vias intracelulares dependentes de PI3K e p38 regula a resposta de macrófagos murinos frente à infecção por Neospora caninum - Mota, Caroline Martins (2013)
Due to the high prevalence and economic importance of neosporosis, the development of safe and effective vaccines against this parasite is crucial to limit abortions and vertical transmission in cattle, as well as to control the spread of oocysts by dogs. Little is known about the innate immune response induced by Neospora caninum, however it follows similar experimental models which activates different intracellular signaling pathways in these cells being critical for the induction of an immune response that restricts the infection. In that sense, the major aim of this study was to determine the role of mitogen-activated protein kinases (MAPKs) signaling p38, JNK and ERK1/2 in macrophages during infection by Neospora caninum. The activation of MAPKs against infection was observed in bone marrow derived macrophages (BMDMs) stimulated with live tachyzoites and different antigenic fractions of N.caninum, which demonstrated a high phosphorylation of p38 MAPK in the early stages. In order to evaluate the biological role elicited by MAPKs during initial contact with N. caninum, BMDMs were pretreated with specific inhibitors. The chemical inhibition of p38 has led to an increased production of IL-12 and expression of co-stimulatory molecules CD80/CD86, coupled with a reduction in levels of IL-10. The relevance of these findings was tested in vivo, it was observed that the challenge of mice immunized with the chemical inhibitor of p38 reduces the parasitic brain load associated with increased proliferative capacity of splenocytes. Aiming to partially discover the molecular mechanism involved in the induction of p38 were conducted additional experiments that demonstrated that the cytokine profile induced by the inhibition of p38 in BMDMs is induced by PI3K. Thus, the results showed that N. caninum manipulates the PI3K/p38 pathway in its favor, in order to downregulate the host s innate immune responses. Therefore, interference in this signaling pathway may be useful for the development of a new vaccine strategy against neosporosis.